Analysis of the influence of the expertise of public auditors, the percentage of the number of independent commissioners, and the percentage of institutional ownership on earnings management in consumer goods industry sub-sector companies in the 2006-2008 - Dimas Reza Hutama (Institute of Accounting Research and Novation (IARN), 2022)
The objectives of this research are to find out empirical evidence of the effect of corporate governance mechanisms on earnings management. The corporate governance mechanisms of this research are auditors with public expertise, composition of independent commissioners and composition of Institutional Ownership. Earning management was estimated by the Utami model. The target population was listed companies in the goods consumption industry sector at the Indonesia Stock Exchange period of 2006-2008. The sample is determined based on purposive sampling method. There were 30 companies meeting the criteria. The research hypothesis was tested using multiple regression analysis. The results of this research show that: (1) auditor public expertise has a significantly negative influence on earnings management; (2) composition of Institutional Ownership had significantly negative influence on earnings management; (3) composition of independent commissioners had no influence on earnings management. The additional result is that the earnings management of the firms which have the competency of the independent commissioners is lower than the earnings management of the firms which have the incompetence of the independent commissioners.